Mammary analogue secretory carcinoma: Update on a new diagnosis of salivary gland malignancy. (9th July 2013) - Sethi, Roshan; Kozin, Elliott; Remenschneider, Aaron; Meier, Josh; VanderLaan, Paul; Faquin, William; Deschler, Daniel; Frankenthaler, Robert
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To review the known histopathologic findings and clinical behavior of mammary analogue secretory carcinoma (MASC). Data Sources PubMed. Review Methods Literature search using the terms "Mammary analogue secretory carcinoma, " "Mammary analog secretory carcinoma, " and "MASC" to identify all relevant publications. Results MASC is an unusual and rare malignant salivary gland tumor first described in 2010. It shares histologic, immunohistochemical, and genetic features with secretory carcinoma of the breast. The clinical behavior of MASC ranges from slowly growing tumors that infrequently recur after surgical resection to aggressive tumors that cause widespread metastasis and death. Many cases of MASC were discovered in archived cases previously classified as acinic cell carcinoma, mucoepidermoid carcinoma, and adenocarcinoma not otherwise specified. Conclusion MASC is a newly recognized variant of salivary gland malignancy. Further research is needed to better delineate its overall prevalence and to define an appropriate treatment algorithm for this new clinical entity. Level of Evidence NA. Laryngoscope, 124:188–195, 2014